2019
DOI: 10.4314/ahs.v19i3.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of glibenclamide, metformin and insulin on fetal pancreatic histology and maternal blood glucose in pregnant streptozotocin-induced diabetic rats

Abstract: Background: Oral hypoglycemic agents use during pregnancy was assumed to cause fetal macrosomia and skeletal deformities, and maternal complications due to significant transfer across placenta or ineffective control of blood glucose.Objective: This study investigated effects of insulin, metformin and glibenclamide on maternal blood glucose; and fetal crown-rump length, gross malformation and pancreatic histology in pregnant streptozotocin-induced diabetic rats.Methods: Twenty-five pregnant rats of groups 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In contrast to this finding, it was reported that the fetal pancreatic tissue for metformin treated mother rats showed preserved structure of pancreatic islets with no signs of degeneration or inflammation. 11 However, this finding might be explained by different doses of metformin, they used the drug in a dose of (36.43 mg/kg) which is much less than the dose used in this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast to this finding, it was reported that the fetal pancreatic tissue for metformin treated mother rats showed preserved structure of pancreatic islets with no signs of degeneration or inflammation. 11 However, this finding might be explained by different doses of metformin, they used the drug in a dose of (36.43 mg/kg) which is much less than the dose used in this study.…”
Section: Discussionmentioning
confidence: 71%
“…8 Metformin was found to induce seminiferous tubules degeneration and atrophy when used with glibenclmide, oral anti-diabetic medication, in non diabetic rats for 21 days. 10,11 The exact mechanism of metformin toxicity in pancreas is not clear. It might be a result of acinar cell degeneration in patients with renal faliure leading to leakage of digestive enzymes from pancreatic ducts to the intercellular space.…”
Section: Introductionmentioning
confidence: 99%
“…The findings also revealed that most 40(60%) of the participants were male and few 27(40%) were female in this study similarly [12] revealed that proportions of males were 54% who had donated blood was significantly higher than females which had 46%. For instance, males are usually heavier than females and are therefore more likely to weigh above 50 kg which is the cut-off weight for donation [29][30][31]. Nearly the highest percentages with 34(52%) participants were bakiga tribe and lowest 13(19%) bafumbira this is because bakiga tribe is native people where the study was carried out.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
“…Although the use of insulin can cause maternal hypoglycemia [118][119][120] and increase maternal weight [121][122][123], it has been shown that insulin when used at therapeutic concentrations does not directly affect the fetus through the placenta [124][125][126], and maternal insulin treatment can reduce poor perinatal prognosis [113,115]. Oral hypoglycemic drugs, such as metformin and glibenclamide, will have some benefits on weight control and insulin sensitivity [127,128], but they can cause giant fetuses and skeletal malformations by entering the fetus through the placenta as well as maternal complications due to the massive transfer between the placenta or ineffective blood glucose control [129][130][131][132].…”
Section: Insulin In Pregnant Patients With Dkdmentioning
confidence: 99%